2012
DOI: 10.5539/ijbm.v7n22p11
|View full text |Cite
|
Sign up to set email alerts
|

Quality Success: Do Organisational Learning Attributes Make a Difference?

Abstract: The purpose of the study is to investigate the learning attributes of organisations following a continuous improvement approach to operations. The focus will be on the examination of organisations with both successful and unsuccessful quality programs to identify organisational learning attributes that discriminate the organisations at either end of the success continuum. Data was collected through a survey sent to Australian organisations certified to quality standard ISO9000. The findings suggest that organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Other studies from around the world have also demonstrated associations between effective knowledge management and business performance (e.g. Andreeva and Kianto, 2012;Oliver, 2012).…”
Section: Business Intelligence and Analyticsmentioning
confidence: 96%
“…Other studies from around the world have also demonstrated associations between effective knowledge management and business performance (e.g. Andreeva and Kianto, 2012;Oliver, 2012).…”
Section: Business Intelligence and Analyticsmentioning
confidence: 96%